STUDY OF MULLET FISH (MUGIL CEPHALUS) CONTAMINATION (BY TOTAL FLORE AND STAPHYLOCOCCUS AUREUS) IN THE GULF OF ANNABA / EAST OF ALGERIA (Sciences & Technologie. C, Biotechnologies, 2012)
In the province of Annaba, mullet fishing represents 36% of pelagic fish sold at the local market [1]. In fact few data were available as well as the the microbiologic quality of this fresh fish distrebuted for the human consumption. This fish frequents lake mouths mostly brakish water. Monthly measuremnets have been undertaken starting from a Mullet fish captured at the golf and to be destrebuted for human consumption. The samples have been analysed during a year of study.The results of the research and the enumeration of Total flora and Staphylococcus aureus bring into prominece the role of Seybouss lake in maintaining a high level of Staphylococcus aureus in area 02. The highly concentrated presence of Staphylococcus aureus menace the health of the consumer especially by thermostable toxins known as staphylococciques.